Об упрощении конструкции высокоточных статических устройств для определения магнитного момента - Пилюгина, Ольга Юрьевна; Пелевин, Дмитрий Евгеньевич; Ерисов, Анатолий Васильевич (НТУ "ХПИ", 2006)
Рассмотрены вопросы упрощения конструкции высокоточных статических устройств для определения магнитного момента технических объектов при сохранении высоких показателей их методической погрешности.

The paper considers questions of simplification of high-precision static apparatus design intended for determination of magnetic moment of technical objects, the simplification maintains good figures of the apparatus truncation error.
Design simplification of high-precision static apparatus for magnetic moment determination
Keywords: многообмоточные статические устройства; первичные преобразователи; обмотки статических устройств; методические погрешности; магнитные потоки; high-precision static apparatus; magnetic moment determination; design simplification